Effects of the freezing process on the proteolysis during the ripening of Port Salut Argentino cheese - Verdini, Roxana Andrea (2005)
The effect of freezing at -30 ºC, frozen storage at -22 ºC for 30 days and thawing at 5 1C on proteolysis during ripening of Port Salut Argentino cheese was studied. Cheeses were sampled at different ripening times (1, 6, 13, 27 and 56 days) and two sampling zones (central andexternal). Moisture content, salt concentration andRP-HPLC of the nitrogenous fractions (water-insoluble fraction, water-soluble fraction and free amino acids in the sulfosalicylic acid-soluble fraction) were analysed. The freezing process did not affect moisture and salt contents at the beginning of the ripening period nor moisture and salt redistribution during the ripening period studied. However, the freezing process affected proteolysis during ripening of Port Salut Argentino cheeses that had been frozen prior to ripening. There was increasedbreakd own of as1-casein and as1-I-casein, and increased breakdown of peptides of the water-soluble fraction (including as1-CN (f1-23)) along with an early development of free amino acids.